Medicare Part D and the Federal Employees Health Benefits Program: A Comparison of Prescription Drug Coverage - Lovett, Annesha (Engage Healthcare Communications, LLC, 2013)
BACKGROUND: There is much debate currently about how to restructure the Medicare program to achieve better value for the money. Many have cited the Federal Employees Health Benefits Program (FEHBP) as a model for reform. OBJECTIVE: To compare drug coverage and cost-sharing between Medicare Part D and the FEHBP plans. METHODS: A cross-sectional comparison was conducted of January 2009 data obtained from the Centers for Medicare & Medicaid Services, the Office of Personnel Management, and 3 health plan websites. Regression analysis and t-tests were used to examine drug coverage, copayment, and coinsurance amounts among Medicare Part D and FEHBP plans. The final study sample of Medicare Part D plans consisted of 19 formularies, covering 63% of total Part D enrollment. These 19 formularies represented 232 stand-alone prescription drug plans. In addition, 5 prescription drug plans or formularies in the FEHBP plans were included, which represents 70% of total FEHBP enrollment. RESULTS: The results of this study reveal that formulary coverage of the top drugs dispensed and sold in the United States in 2009 ranged from 72% to 94% (average, 84%) in Medicare Part D plans and from 85% to 99% (average, 94%) in the FEHBP plans (P <.01). The mean copayment for generic drugs in Medicare Part D plans was $4.53 compared with a mean of $7.67 (P <.05) in the FEHBP plans. The difference between the 2 programs in mean copayment for brand-name drugs was nonsignificant. For generic drugs, the mean coinsurance rate was 17% for Medicare Part D plans and a mean of 20% for the FEHBP plans (P <.05). CONCLUSIONS: This analysis shows that there are differences in prescription drug coverage and cost-sharing among plans within Medicare Part D and the FEHBP. To avoid extreme increases in payroll taxes and other revenues or major cutbacks in services, Medicare must explore ways to change the healthcare system to achieve better value for the money. The experience of the FEHBP suggests a possible means of accomplishing this objective.